Wide-temperature-range crack pouring adhesive based on rubber modified asphalt and preparation method of wide-temperature-range crack pouring adhesive

By using rubber-modified asphalt, basalt fibers and other additives in the filling glue, combined with the response surface method to optimize the process, the problem of insufficient performance of the filling glue in the Northeast under extreme temperature differences is solved, and the high and low temperature performance and construction performance have been significantly improved.

CN119529761APending Publication Date: 2025-02-28JILIN TRAFFIC SCI ACAD +1
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411592240.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Asphalt pavement in the Northeast region is caused by cracks, ruts and pits due to factors such as climate, traffic volume and heavy load. The existing seam filling glue cannot have the performance of high temperature not flowing and low temperature not cracking at the same time under extreme temperature differences, resulting in a shortened service life.

Method used

The wide-temperature filling glue based on rubber-modified asphalt is used. By adding basalt fibers, SBS, furfural extraction oil and dibutyl phthalate, the material ratio and preparation process are optimized through the response surface method to improve the high and low temperature performance and construction performance of the filling glue.

Benefits of technology

It significantly improves the high and low temperature performance, anti-aging performance and anti-freeze-thaw cycle performance of the seam filling glue, extends the service life of the road, reduces maintenance costs, and maintains good road performance under different temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529761A_ABST
    Figure CN119529761A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of road engineering materials, and discloses a wide-temperature-range crack pouring adhesive based on rubber modified asphalt and a preparation method thereof.The wide-temperature-range crack pouring adhesive is prepared by taking the rubber modified asphalt as a matrix through a response surface method and adding SBS, basalt fibers and a modifier. The performance of the material is tested through a conventional test, and meanwhile, a test with more characteristics in northeast regions is provided, and the performance of the material is detected through injection depth, viscosity, low-temperature stretching after aging and freeze-thaw cycle stretching. Results show that a test designed by a response surface method has very strong reliability, and the modified heating type crack pouring adhesive added with the basalt fiber can significantly improve the high and low temperature performance of the crack pouring adhesive, and also has good anti-aging performance and freeze-thaw cycle resistance. And the filling depth and the viscosity of the sealant are not obviously lower than those of the same type of sealant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of road engineering materials, and in particular relates to a wide-temperature range caulking adhesive based on rubber-modified asphalt and a preparation method thereof. Background Art

[0002] Asphalt pavement is widely used in road engineering construction because of its short construction period, comfortable driving, low noise, and recyclability. However, asphalt pavements in the Northeast are often affected by factors such as climate, traffic volume, and heavy loads, resulting in cracks, rutting, potholes and other defects on its surface, which seriously affect its service life. Therefore, timely sealing of cracks with sealing materials is the most effective method in road maintenance. Among them, asphalt-based heated caulking glue is currently the most widely used caulking material in the Northeast. However, due to the high summer road surface temperature in the Northeast and the low winter temperature of 30°C, many caulking glues cannot simultaneously have the performance of not flowing at high temperatures and not cracking at low temperatures under such huge temperature difference conditions. Therefore, the development of a wide temperature range asphalt-based caulking glue suitable for the Northeast has become a difficult problem that needs to be solved urgently in road maintenance projects in cold regions.

[0003] Many studies have modified asphalt-based caulking adhesive by introducing different polymers. Among them, the most commonly used ones are ethylene butadiene styrene (SBS), styrene polyethylene butadiene styrene (SEBS) and other types of block copolymers. A large number of research results show that the use of a single modifier often cannot achieve the best modification effect, and composite modification has become the first choice for research. Among them, SBS forms a three-dimensional network structure inside the matrix asphalt, which makes the modified asphalt have good high and low temperature resistance and elasticity, and also improves the low-temperature tensile performance to meet the needs of caulking adhesive. However, the content of SBS modifier needs to be strictly controlled. The compatibility and stability of high-content SBS-modified asphalt caulking adhesive are relatively poor, while too low a content will make the performance of the caulking adhesive insufficient. Some studies use methods such as adding softeners and compatibilizers to enhance the compatibility of modified asphalt caulking adhesives, but practice has shown that this type of caulking adhesive can usually only last for one year. It can be seen that the composite modified asphalt caulking adhesive has serious deficiencies in low-temperature performance. With the promotion of waste rubber recycling and fiber reinforcement technology, new ideas have been provided for the research of modified asphalt joint sealants. In particular, rubber modified asphalt has good deformation resistance and low-temperature crack resistance. Polyurethane fiber, lignin fiber, asbestos fiber and glass fiber also play different advantages in asphalt modification. Among them, basalt fiber not only has the functions of corrosion resistance and UV resistance, but also effectively inhibits the generation of cracks because basalt fiber can form a three-dimensional fiber network in asphalt, and the fiber network can play the role of reinforcement and bridging, thereby effectively improving the high temperature performance (softening point, dynamic viscosity) and low temperature performance of asphalt, and improving the elastic modulus of asphalt. In view of this, this paper takes rubber modified asphalt as the matrix, adds SBS, basalt fiber and other additives as modifiers, prepares a wide temperature range rubber-based asphalt joint sealant suitable for the Northeast region, and tests the road performance of the joint sealant by cone penetration, compression elastic recovery rate, low-temperature tensile test, etc., to provide theoretical basis and data reference for the relevant research and application of asphalt pavement joint sealants in cold areas.

[0004] However, in order to evaluate the applicability of the prepared caulking glue in crack repair, a series of performance evaluations are required. Some scholars proposed using DTT to test and evaluate the bonding performance of caulking glue, and on this basis, they improved and optimized the test parameters and proposed to use strain energy density as a low-temperature performance index. Later, they redesigned the fixture and sample based on this and proposed a direct tensile (CSADT) test to simulate the cracking of caulking glue. Later, some scholars proposed using stress relaxation index to evaluate the low-temperature performance of caulking glue. In general, the current research on caulking glue focuses on low-temperature performance, that is, the research on the performance of caulking glue does not take into account regional factors, that is, the climate and other conditions in each region are not the same, that is, the climate in the Northeast region is relatively large, there is a strong freeze-thaw cycle in spring and winter, and the large temperature difference between day and night will affect the performance of caulking glue.

[0005] Through the above analysis, the problems and defects of the prior art are as follows:

[0006] Timely repair of road cracks is an important measure for pavement maintenance. Heated caulking glue is the most commonly used crack repair material. However, in the Northeast, due to the lower winter temperatures and higher ground temperatures in summer, the caulking glue is always damaged prematurely, which causes great trouble to road users and shortens the service life of the road. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a wide-temperature range caulking adhesive based on rubber-modified asphalt and a preparation method thereof.

[0008] The present invention is achieved in that a wide temperature range caulking adhesive based on rubber modified asphalt comprises:

[0009] The matrix material is rubber modified asphalt, and the additives are basalt fiber, rubber powder, SBS, dibutyl phthalate, and furfural extracted oil.

[0010] Another object of the present invention is to provide a method for preparing a wide temperature range caulking adhesive based on rubber modified asphalt, comprising the following steps:

[0011] Step 1, placing the rubber modified asphalt in an oven and heating it at 150° C. to a fluid state;

[0012] Step 2, furfural extraction oil and dibutyl phthalate, wherein 7% of asphalt content is selected as the admixture because the severe cold type caulking adhesive to be prepared is selected; add the sample, and stir at a speed of 800r / min for 30min in a high-speed stirring disperser at 165-175°C;

[0013] Step 3, adding SBS to the sample in batches, stirring at a speed of 2000 r / min for 30 min in a high-speed stirring disperser at 165° C. to 175° C.;

[0014] Step 4, shearing the sample at a speed of 4000 r / min for 45 min on a high-speed stirring disperser at 175° C.;

[0015] Step 5: Add basalt fibers to the sample in batches, and shear the sample at a speed of 4500 r / min to 5000 r / min for at least 30 minutes on a high-speed stirring disperser at 175° C. to 180° C. to ensure that there are no obvious impurities and suspension.

[0016] Another object of the present invention is to provide a preparation system of a wide temperature range caulking adhesive for rubber modified asphalt, comprising:

[0017] A heating module is used to place the rubber-modified asphalt in an oven and heat it to a fluid state at 150°C;

[0018] A stirring module is used to mix furfural extraction oil and dibutyl phthalate, wherein 7% of asphalt content is selected as the mixing amount because the severe cold type joint filling adhesive to be prepared is selected; add the sample, and stir it at a speed of 800r / min for 30min on a high-speed stirring disperser at 165-175℃; add SBS to the sample in batches, and stir it at a speed of 2000r / min for 30min on a high-speed stirring disperser at 165-175℃;

[0019] The shearing module is used to shear the sample at a speed of 4000r / min for 45min on a high-speed stirring and dispersing machine at 175℃; the basalt fibers are added to the sample in batches, and the sample is sheared at a speed of 4500r / min to 5000r / min for at least 30min on a high-speed stirring and dispersing machine at 175℃ to 180℃ to ensure that there are no obvious impurities and suspension;

[0020] The optimization module is used to optimize the experimental process through response surface methodology.

[0021] Furthermore, the response surface methodology:

[0022] Assume that there is a relationship between a corresponding value and multiple influencing factors:

[0023] y=f(x1,x2,…,x k )+ε (1)

[0024] In the formula, y is the response value, x1, x2, ..., x k is the influencing factor, ε is a random variable;

[0025] y=β0+β1x1+β2x2+…+β k x k +ε (2)

[0026] In the equation, β i is the impact factor x i The slope

[0027] Use the above formula to fit the influencing factors. If the fitting is successful, select the appropriate influencing factors to obtain the best response value. If y and x are found i If the linear Taylor expansion cannot be used between them, then it is necessary to perform a second-order transformation on equation (2) to obtain the following equation:

[0028]

[0029] In this formula, β i is x i The linear effect of ijis the interaction among the independent variables, B ii It is a secondary effect;

[0030] This can be represented using a matrix

[0031] Y=β0+X′b+X′BX+ε (4)

[0032] In this equation, X = (x1, x2, ..., x k ) T ; b = (β1, β2, ..., β k ) T , is its regression coefficient matrix B is a K-order symmetric matrix

[0033] When the response reaches the optimal value, the following equation is satisfied

[0034]

[0035] The solution X in equation (5) is called a stable point, and it is transformed

[0036]

[0037] Substituting formula (6) into formula (4), we can get the predicted response value of the stable point:

[0038]

[0039] There are many design models based on response surface analysis. Select the appropriate response surface design according to the experimental requirements.

[0040] Another object of the present invention is to provide a computer device, comprising a memory and a processor, wherein the memory stores a computer program, and when the computer program is executed by the processor, the processor executes the steps of the method for preparing the wide temperature range caulking adhesive for rubber-modified asphalt.

[0041] Another object of the present invention is to provide a computer-readable storage medium storing a computer program, which, when executed by a processor, enables the processor to execute the steps of the method for preparing the wide-temperature range caulking adhesive for rubber-modified asphalt.

[0042] Another object of the present invention is to provide an information data processing terminal, which is used to implement a preparation system for the wide temperature range caulking glue of the rubber-modified asphalt.

[0043] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0044] First, the present invention overcomes the problem that traditional caulking glue is prone to failure under the extreme climatic conditions in the Northeast region by introducing basalt fibers to form a three-dimensional network structure, especially significantly improving low-temperature crack resistance and high-temperature stability.

[0045] Filling the technological gap: This invention combines basalt fiber with SBS and furfural extracted oil for the first time in the preparation of asphalt caulking adhesive, which effectively improves the comprehensive performance of the caulking adhesive and fills the technological gap in caulking adhesive used in severe cold areas at home and abroad.

[0046] A technological breakthrough has been achieved: Through the optimization of the response surface methodology, the present invention not only significantly improves the high and low temperature performance of the caulking glue, but also has excellent workability and durability, enabling it to demonstrate outstanding economic and technical value in practical applications.

[0047] Through detailed experimental design and data analysis, the present invention has demonstrated its excellent practicality and technical effects under severe cold conditions, and is expected to play an important role in the field of road maintenance.

[0048] The present invention uses the response surface method to prepare a wide temperature range caulking adhesive by adding SBS, basalt fiber and modifier with rubber modified asphalt as the matrix. While testing its performance through conventional tests, it also proposes a test more characteristic of the Northeast region, which tests its performance by injection depth, viscosity, low-temperature stretching after aging and freeze-thaw cycle stretching. The results show that the experiment designed by the response surface method has strong reliability. The modified heated caulking adhesive with basalt fiber added can significantly improve the high and low temperature performance of the caulking adhesive, and has good anti-aging performance and anti-freeze-thaw cycle performance. And its injection depth and viscosity are not significantly inferior to the same type of caulking adhesive.

[0049] Second, the expected benefits and commercial value of the technical solution of the present invention after transformation are:

[0050] The present invention optimizes the preparation process of the caulking glue to enable it to have excellent performance under extreme conditions of high and low temperatures. It is expected that this technical solution can significantly extend the service life of roads and reduce road maintenance costs, especially in areas with harsh climates such as the Northeast. The commercial value is reflected in the fact that by improving product performance, the market share can be expanded, the product competitiveness can be enhanced, and considerable economic benefits can be brought about. In addition, the innovativeness and environmental protection of the technology have also won it a good market reputation, and it is expected to bring long-term revenue growth to related companies.

[0051] The technical solution of the present invention fills the technical gap in the industry at home and abroad:

[0052] At present, the performance of the caulking glue on the market is poor in dealing with extreme climate change in Northeast China, especially in terms of low-temperature crack resistance and high-temperature fluidity resistance. The present invention combines basalt fiber with SBS and furfural extracted oil for the first time, and successfully prepares a caulking glue suitable for a wide temperature range, filling the technical gap of high-performance caulking glue used in severe cold areas in the industry, and providing a new solution for the field of road maintenance materials.

[0053] The technical solution of the present invention solves a technical problem that people have been eager to solve but have never succeeded in solving: the present invention successfully solves the problem that traditional caulking glue cannot have both high-temperature stability and low-temperature crack resistance in severely cold regions such as the Northeast. By optimizing the material ratio and preparation process, the present invention significantly improves the comprehensive performance of the caulking glue, so that it can maintain excellent road performance under extreme climatic conditions. This breakthrough has not been successfully achieved in past research, and provides reliable technical support for road maintenance in cold regions.

[0054] The technical solution of the present invention overcomes technical prejudice: the present invention overcomes the reliance on a single modifier (such as SBS) in traditional technology in terms of material selection and process optimization, innovatively introduces a combination of basalt fiber and other additives, and successfully overcomes the compatibility and stability issues in the preparation of composite materials through optimization using the response surface methodology. In addition, a series of experiments have verified the feasibility and superiority of the technical solution, effectively overcoming the technical prejudice of the industry for the application of new materials and demonstrating strong innovation potential.

[0055] Third, the performance of traditional caulking glue materials is often unstable under extreme temperature conditions. For example, it is easy to soften and flow at high temperatures, but it is easy to become brittle and crack at low temperatures, resulting in a short-lasting repair effect. It is difficult for the existing technology to maintain the elasticity and strength of the material at the same time over a wide temperature range. The present invention significantly improves the temperature adaptability of the caulking glue by precisely controlling the ratio of rubber-modified asphalt, adding furfural extracted oil and dibutyl phthalate as plasticizers, and adding appropriate amounts of SBS and basalt fiber. By performing high-speed stirring and shearing in the range of 150°C to 180°C, the material maintains flexibility at low temperatures and still has sufficient strength at high temperatures, solving the problem of unstable performance of the caulking glue over a wide temperature range.

[0056] In crack repair on roads and airport runways, caulking materials need to withstand mechanical stress and temperature changes for a long time. The durability of traditional materials is often insufficient and easily affected by the environment, resulting in repeated cracks and increased maintenance costs. The present invention significantly enhances the durability and tear resistance of the caulking adhesive by adding basalt fibers in batches and performing high-speed shearing at high temperatures to fully mix the fibers with modified asphalt. The addition of basalt fibers not only improves the mechanical strength of the material, but also improves the material's fatigue resistance, allowing the caulking adhesive to remain stable under frequent stress, reducing the rate of material aging and performance degradation.

[0057] During the construction process, especially under low temperature conditions, traditional caulking glue often shows poor fluidity and operability, resulting in uneven filling and poor joint effect, which increases the construction difficulty and rework rate. The present invention optimizes the dosage ratio of furfural extracted oil and dibutyl phthalate, combined with the addition of SBS and basalt fiber, to ensure that the caulking glue has good fluidity at high temperatures and maintains suitable operability at low temperatures. Through the refined control of the material, the construction performance of the caulking glue is significantly improved, so that it can achieve uniform and stable crack filling effects under different temperature conditions.

[0058] During the preparation process of traditional caulking materials, problems such as uneven distribution of material components and difficulty in removing impurities often occur, resulting in unstable product quality and affecting the actual application effect. The present invention ensures the full mixing of the components by repeatedly stirring and shearing the materials at high speed during the preparation process, and eliminates impurities and suspended matter in the sample by optimizing the stirring speed and time, thereby ensuring the uniformity and purity of the caulking glue. This method significantly improves the quality control level of material preparation and ensures the stability and consistency of the final product. By optimizing the material formula and preparation process, the present invention has made significant technological progress in the temperature adaptability, durability, construction performance and preparation uniformity of the caulking glue, successfully solved many key problems in the prior art, and provided strong technical support for the industrial application of caulking materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 It is a flow chart of a method for preparing a wide-temperature range caulking adhesive based on rubber-modified asphalt provided in an embodiment of the present invention.

[0060] Figure 2 It is a structural block diagram of a system for preparing a wide temperature range caulking adhesive based on rubber-modified asphalt provided in an embodiment of the present invention.

[0061] Figure 3 This is a diagram of (a) basalt fiber (b) SBS modifier (c) dibutyl phthalate (d) furfural extracted oil provided by an embodiment of the present invention.

[0062] Figure 4 This is a basic flow chart for preparing basalt fiber modified crack caulking adhesive provided in an embodiment of the present invention.

[0063] Figure 5 It is a normal distribution diagram based on standardized residuals provided in an embodiment of the present invention.

[0064] Figure 6 It is a normal distribution diagram based on standardized residuals provided in an embodiment of the present invention.

[0065] Figure 7 is a residual distribution diagram provided by an embodiment of the present invention.

[0066] Figure 8 It is a comparison chart of predicted values ​​and actual values ​​provided by an embodiment of the present invention.

[0067] Fig. 9 Softening point response surface provided by the embodiment of the present invention: (a) factors: EC and SC; (b) factors BFC and SC diagram.

[0068] Fig.10 The cone penetration response surface provided by the embodiment of the present invention includes (a) factors: EC and SC; (b) factors: BFC and SC; (c) factors: BFC and EC.

[0069] Fig.11 : This is a diagram of the compression elastic recovery rate provided by an embodiment of the present invention: (a) factors: BFC and EC (b) factors: BFC and SC (c) factors: EC and BFC.

[0070] Fig.12 These are the comparison diagrams of low-temperature stretching before and after aging provided by the embodiments of the present invention (a) cycle 1, (b) cycle 2, and (c) cycle 3.

[0071] Fig.13 This is a comparison diagram of low-temperature stretching after three cycles provided by an embodiment of the present invention.

[0072] Fig.14 It is a viscosity-temperature curve diagram provided by an embodiment of the present invention.

[0073] Fig.15 This is an injection depth map provided by an embodiment of the present invention.

[0074] Fig.16 (a) A, (b) B, (c) C, (d) D are graphs showing the changes in adhesion during freeze-thaw cycles provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0075] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0076] The following are two specific industrial application embodiments of the method for preparing the wide temperature range crack filling glue based on rubber modified asphalt according to the present invention:

[0077] Example 1: Highway crack repair

[0078] Due to the high frequency of vehicle traffic and extreme weather, road cracks are a common problem on highways. Traditional caulking materials tend to lose elasticity under low temperature conditions, causing cracks to reappear, increasing maintenance costs and safety risks. Especially in cold regions, the low-temperature performance of materials is crucial.

[0079] 1) Material preparation: According to the preparation method of the present invention, a crack filling glue with high elasticity and low temperature resistance is prepared to ensure its long-term and stable use in highway crack repair.

[0080] 2) Application and construction: In the crack repair construction of highways, the caulking glue material of the present invention is used, and the material is evenly filled into the cracks through a caulking machine and cured at an appropriate temperature.

[0081] 3) Effect evaluation: The repaired cracks showed good stability in both low winter temperatures and high summer temperatures, and the caulking glue did not crack or peel, effectively extending the service life of the road.

[0082] By using the wide temperature range crack filling adhesive of the present invention, the crack repair work on the highway is significantly improved, the recurrence of cracks is reduced, the maintenance frequency and cost are reduced, and the safety and traffic capacity of the road are improved.

[0083] Example 2: Airport runway crack repair

[0084] Airport runways are subject to strong mechanical stress and temperature changes due to frequent aircraft takeoffs and landings, which can easily cause cracks. Since airport runways require extremely high safety and durability, repair materials need to have excellent high and low temperature adaptability and good fatigue resistance.

[0085] Implementation steps:

[0086] 1) Material preparation: The preparation method of the present invention is used to produce a high-durability wide-temperature range caulking adhesive, and its fatigue resistance and temperature adaptability are particularly enhanced to meet the high standard requirements for airport runway repair.

[0087] 2) Application and construction: In the crack repair of the airport runway, the caulking glue material of the present invention is used to fill the cracks according to the standard construction process, and ensure that the material is fully cured.

[0088] 3) Effect evaluation: The repaired runway remained intact under the high-frequency aircraft takeoff and landing pressure, and the caulking adhesive showed excellent compressive resistance and temperature adaptability, with no material degradation or performance decline.

[0089] By using the caulking adhesive material of the present invention, the crack repair quality of the airport runway is greatly improved, the material maintains good performance under extreme temperature conditions, ensures the safety and continuity of airport operations, and reduces the frequency and cost of runway maintenance caused by cracks.

[0090] The wide temperature range caulking adhesive based on rubber-modified asphalt provided in an embodiment of the present invention comprises:

[0091] The matrix material is rubber modified asphalt, and the additives are basalt fiber, rubber powder, SBS, dibutyl phthalate, and furfural extracted oil.

[0092] like Figure 1 As shown, a method for preparing a wide temperature range caulking adhesive based on rubber modified asphalt provided in an embodiment of the present invention comprises the following steps:

[0093] Step 1, placing the rubber modified asphalt in an oven and heating it at 150° C. to a fluid state;

[0094] Step 2, furfural extraction oil and dibutyl phthalate, wherein 7% of asphalt content is selected as the admixture because the severe cold type caulking adhesive to be prepared is selected; add the sample, and stir at a speed of 800r / min for 30min in a high-speed stirring disperser at 165-175°C;

[0095] Step 3, adding SBS to the sample in batches, stirring at a speed of 2000 r / min for 30 min in a high-speed stirring disperser at 165° C. to 175° C.;

[0096] Step 4, shearing the sample at a speed of 4000 r / min for 45 min on a high-speed stirring disperser at 175° C.;

[0097] Step 5: Add basalt fibers to the sample in batches, and shear the sample at a speed of 4500 r / min to 5000 r / min for at least 30 minutes on a high-speed stirring disperser at 175° C. to 180° C. to ensure that there are no obvious impurities and suspension.

[0098] The preparation method of the wide-temperature range caulking adhesive based on rubber-modified asphalt provided in the embodiment of the present invention achieves the excellent performance of the caulking adhesive in a wide temperature range through multi-step fine processing. First, in step 1, the rubber-modified asphalt is placed in an oven and heated to a fluid state at a temperature of 150°C. This step ensures that the asphalt can be evenly mixed in liquid form in subsequent operations, laying the foundation for the subsequent addition step.

[0099] Then, in step 2, furfural extracted oil and dibutyl phthalate were added to the sample as plasticizers, and the selected dosage was 7% of the asphalt content, which was based on the requirements for preparing severe cold-type caulking glue. The sample was stirred at a speed of 800r / min for 30 minutes on a high-speed stirring disperser at 165℃ to 175℃ to ensure that the plasticizer and modified asphalt were fully mixed, so that the caulking glue had better flexibility and crack resistance at low temperatures.

[0100] Subsequently, in step 3, SBS (styrene-butadiene-styrene block copolymer) was added to the sample in batches and stirred at 2000r / min for 30 minutes on a high-speed stirring disperser at 165°C to 175°C. The addition of SBS gives the caulking glue better elasticity and fatigue resistance, and can maintain stable performance over a large temperature range. This process ensures that SBS is evenly distributed in the asphalt matrix through high-speed stirring, thereby enhancing the mechanical properties of the caulking glue.

[0101] Finally, in step 4 and step 5, the sample is sheared at a speed of 4000r / min and 4500r / min to 5000r / min, respectively. In step 4, the sample is sheared for 45 minutes to further refine the particle structure in the mixture. In step 5, basalt fiber is gradually added and shearing is continued for at least 30 minutes. The addition of basalt fiber enhances the strength and tear resistance of the caulking adhesive. At the same time, the shearing process ensures that there are no obvious impurities and suspended matter in the sample, so that the caulking adhesive has good uniformity and stability during construction and use.

[0102] Through the above steps, the present invention realizes a method for preparing a high-performance wide-temperature range caulking adhesive, which significantly improves the adaptability and durability of the caulking adhesive under different temperature conditions and provides an excellent material choice for road maintenance and repair.

[0103] like Figure 2 As shown, a preparation system of a wide temperature range caulking adhesive for rubber-modified asphalt provided in an embodiment of the present invention comprises:

[0104] A heating module is used to place the rubber-modified asphalt in an oven and heat it to a fluid state at 150°C;

[0105] A stirring module is used to mix furfural extraction oil and dibutyl phthalate, wherein 7% of asphalt content is selected as the mixing amount because the severe cold type joint filling adhesive to be prepared is selected; add the sample, and stir it at a speed of 800r / min for 30min on a high-speed stirring disperser at 165-175℃; add SBS to the sample in batches, and stir it at a speed of 2000r / min for 30min on a high-speed stirring disperser at 165-175℃;

[0106] The shearing module is used to shear the sample at a speed of 4000r / min for 45min on a high-speed stirring and dispersing machine at 175℃; the basalt fibers are added to the sample in batches, and the sample is sheared at a speed of 4500r / min to 5000r / min for at least 30min on a high-speed stirring and dispersing machine at 175℃ to 180℃ to ensure that there are no obvious impurities and suspension;

[0107] The optimization module is used to optimize the experimental process through response surface methodology.

[0108] The response surface method provided by the embodiment of the present invention is as follows:

[0109] Assume that there is a relationship between a corresponding value and multiple influencing factors:

[0110] y=f(x1,x2,…,x k )+ε(1)

[0111] In the formula, y is the response value, x1, x2,…, x k is the influencing factor, ε is a random variable;

[0112] y=β0+β1x1+β2x2+…+β k x k +ε(2)

[0113] In the equation, β i is the impact factor x i The slope

[0114] Use the above formula to fit the influencing factors. If the fitting is successful, select the appropriate influencing factors to obtain the best response value. If y and x are found i If the linear Taylor expansion cannot be used between them, then it is necessary to perform a second-order transformation on equation (2) to obtain the following equation:

[0115]

[0116] In this formula, β i is x i The linear effect of ij is the interaction among the independent variables, B ii It is a secondary effect;

[0117] This can be represented using a matrix

[0118] Y=β0+X′b+X′BX+ε(4)

[0119] In this equation, X = x1, x2, ..., x k T ; b = β1, β2, …, β k T , is its regression coefficient matrix B is a K-order symmetric matrix

[0120] When the response reaches the optimal value, the following equation is satisfied

[0121]

[0122] The solution X in equation (5) is called a stable point, and it is transformed

[0123]

[0124] Substituting formula (6) into formula (4), we can get the predicted response value of the stable point:

[0125]

[0126] There are many design models based on response surface analysis. Select the appropriate response surface design according to the experimental requirements.

[0127] Another object of the present invention is to provide a computer device, comprising a memory and a processor, wherein the memory stores a computer program, and when the computer program is executed by the processor, the processor executes the steps of the method for preparing the wide temperature range caulking adhesive for rubber-modified asphalt.

[0128] Another object of the present invention is to provide a computer-readable storage medium storing a computer program, which, when executed by a processor, enables the processor to execute the steps of the method for preparing the wide-temperature range caulking adhesive for rubber-modified asphalt.

[0129] Another object of the present invention is to provide an information data processing terminal, which is used to implement a preparation system for the wide temperature range caulking glue of the rubber-modified asphalt.

[0130] The present invention is specifically implemented:

[0131] 1. The present invention uses the response surface methodology to prepare a wide temperature range caulking adhesive by adding SBS, basalt fiber and modifier to rubber modified asphalt as a matrix. While testing its performance through conventional tests, it also proposes tests that are more characteristic of the Northeast region, such as injection depth, viscosity, low-temperature stretching after aging, and freeze-thaw cycle stretching to detect its performance. The results show that the experiment designed by the response surface methodology has strong reliability. The modified heated caulking adhesive with basalt fiber added can significantly improve the high and low temperature performance of the caulking adhesive, and also has good anti-aging performance and anti-freeze-thaw cycle performance. And its injection depth and viscosity are not significantly inferior to the same type of caulking adhesive.

[0132] 2 Materials and experimental design

[0133] 2.1. Materials

[0134] In previous studies, it was found that rubber modified asphalt has good advantages, such as good construction performance, appropriate high temperature performance, low temperature crack resistance and certain fatigue resistance, so it has been widely used in roads [39–42]. Rubber modified asphalt is modified by wet method, in which the components are dispersed and mixed by high-speed shearing machine, and the rubber content is 20%. The main properties of rubber modified asphalt are evaluated according to relevant standards. The specific properties are shown in Table 1.

[0135] Basalt fiber is a new type of environmentally friendly material that is gradually emerging. It is made of basalt and has a tensile strength range of 4000-4850Mpa. At the same time, basalt fiber also has excellent weather resistance and can work well at low temperatures. It has excellent corrosion resistance, UV resistance, chemical stability and flame retardancy. In previous studies, it was found that basalt modified asphalt mortar has good working performance and road performance, that is, certain low-temperature crack resistance and fatigue resistance. The specific physical properties are shown in Table 2

[0136] The heating type caulking glue used for pavement cracks in this study is a cold type caulking glue, the matrix material is rubber modified asphalt, and the additives are basalt fiber, rubber powder, SBS, dibutyl phthalate, furfural extracted oil,

[0137] Table 1 Related properties of rubber modified asphalt

[0138]

[0139] Table 2 Main properties of basalt fiber

[0140] like Figure 3 (a)

[0141]

[0142] Table 3 Main physical properties of SBS

[0143] like Figure 3 (b)

[0144]

[0145] Table 4 Main properties of dibutyl phthalate

[0146] like Figure 3 (c)

[0147]

[0148] Table 5 Main properties of furfural extracted oil

[0149] like Figure 3 (d)

[0150]

[0151] 2.2 Preparation of caulking glue

[0152] The base asphalt used in this study is 20% rubber modified asphalt. (1) The rubber modified asphalt is placed in an oven and heated to a fluid state at 150°C. (2) Furfural extraction oil and dibutyl phthalate are added. Because the product to be prepared is a severe cold-type caulking adhesive, 7% of the asphalt content is selected as the admixture. Add the sample and stir it at a speed of 800r / min for 30min in a high-speed stirring disperser at 165-175°C. (3) Add SBS to the sample in batches and stir it at a speed of 2000r / min for 30min in a high-speed stirring disperser at 165-175°C. (4) Shear the sample at a speed of 4000r / min for 45min in a high-speed stirring disperser at 175°C. (5) Add basalt fiber to the sample in batches and shear the sample at a speed of 4500r / min-5000r / min for at least 30min in a high-speed stirring disperser at 175-180°C to ensure that there are no obvious impurities and suspension. The basic process is as follows: Figure 4 Shown

[0153] 2.3 Response surface methodology

[0154] Each experiment consists of experimental design and data analysis. The data analysis method depends on the experimental design. Today, experimental design and various application software developed for this purpose can quickly and reliably perform experimental design and data analysis.

[0155] The design method of response surface experiment was originally used to optimize the biological test process. When there are multiple influencing factors in the experiment, the relationship between the influencing factors can be obtained by using the regression design method. In this way, the test process can be optimized. If random errors are taken into account, this test method can reduce the number of test points and the amount of test. After obtaining the test results, the test results are fitted, and finally a continuous variable regression surface model can be established to obtain the optimal range of influencing factors. Compared with the traditional orthogonal experiment, its response surface is a continuous surface model with better intuitiveness. At the same time, the model can also predict points outside the test range through the regression equation. The response surface method is constructed on the basis of the least squares method. The optimization process is as follows:

[0156] The first step is to assume that there is a relationship between a corresponding value and multiple influencing factors:

[0157] y=f(x1,x2,…,x k )+ε(1)

[0158] In the formula, y is the response value, x1, x2,…, x k is the influencing factor and ε is a random variable.

[0159] y=β0+β1x1+β2x2+…+β k x k +ε(2)

[0160] In the equation, β i is the impact factor x i The slope

[0161] Use the above formula to fit the influencing factors. If the fitting is successful, select the appropriate influencing factors to obtain the best response value. If y and x are found i If the linear Taylor expansion cannot be used between them, then it is necessary to perform a second-order transformation on equation (2) to obtain the following equation:

[0162]

[0163] In this formula, β i is x i The linear effect of ij is the interaction among the independent variables, B ii It's a secondary effect.

[0164] This can be represented using a matrix

[0165] Y=β0+X′b+X′BX+ε(4)

[0166] In this equation, X = x1, x2, ..., x k T; b = β1, β2, …, β k T , is its regression coefficient matrix B is a K-order symmetric matrix

[0167] When the response reaches the optimal value, the following equation is satisfied

[0168]

[0169] The solution X in equation (5) is called a stable point, and it is transformed

[0170]

[0171] Substituting formula (6) into formula (4), we can get the predicted response value of the stable point:

[0172]

[0173] There are many design models based on response surface analysis. Select the appropriate response surface design according to the experimental requirements.

[0174] According to the relevant literature, the dosage of SBS in asphalt is generally about 6% in order to have good compatibility [24, 25, 43]. However, considering that the caulking glue used in this design is a severe cold type caulking glue with an applicable use temperature of 30°C and furfural extract oil and dibutyl phthalate (DOP) were added as solubilizers in this test, the design dosage of SBS is 8% to 10%, and the dosage of furfural extract oil as a solubilizer for SBS is set at 1316%. The dosage of basalt fiber is selected from the reference literature as 1% to 4%. According to the relevant literature, dibutyl phthalate (DOP) can significantly improve the low temperature performance of asphalt [44–46]. The dosage in this test is fixed at 7%. Table

[0175]

[0176] This experiment uses DesignExpert13.0 software as the design program, which is used for experimental design response surface modeling, statistical experimental regression process and process optimization.

[0177] 2.4 Experiments with response settings

[0178] 2.4.1 Cone penetration

[0179] The cone penetration test is used to evaluate the ability of heated caulking glue to resist the invasion of foreign matter. In the test, the standard needle of the asphalt needle penetration instrument is replaced with a standard cone to measure the cone penetration of the caulking glue. Pour the caulking glue into a sample dish with a diameter of 70mm and a depth of 45mm. After cooling for two hours, place it in 25℃±5℃ water to cool. After zeroing, the cone falls freely for 5 seconds and the penetration depth is recorded (with an accuracy of 0.1mm). Each sample is measured three times and the average of the three measurements is the result.

[0180] 2.4.2 Softening point

[0181] Softening point is a key indicator for evaluating the high temperature performance of heated caulking adhesive. The softening point of heated caulking adhesive is usually greater than 80°C. Place the sample, sample ring, metal bracket, etc. in a 32±1°C glycerol tank for preheating for 15 minutes, then heat at a rate of 5°C / min±0.5°C / min, record the temperature at which the sample softens and falls, test each sample twice and take the average value as the result, with an accuracy of 0.5°C.

[0182] 2.4.3 Compression elastic recovery rate

[0183] The compression elastic recovery rate can indirectly reflect the ability of the heated caulking adhesive to recover deformation under vehicle load and low temperature, as well as the flexibility of the material under pressure and low temperature conditions. The test uses an asphalt penetrometer, and the standard needle is replaced by a standard penetration ball. The specimen is placed in a large weighing dish with an inner diameter of 70mm and a depth of 45mm at 25±5℃ for 2h, and then the scale is returned to zero, allowing the penetration ball to fall freely. The penetration time is 5 seconds.

[0184] The penetration depth after 5 seconds is recorded as the initial penetration depth P. Then the connecting rod is tightened so that the penetration ball penetrates 10 mm into the sample at a constant speed within 10 seconds. The total penetration is recorded as P+100. After being fixed for 5 seconds, the penetration ball is allowed to rebound on the surface of the specimen for 20 seconds. The compression elastic recovery rate can be calculated by the following equation (8)

[0185]

[0186] Where r is the compression elastic recovery rate (%); P is the initial penetration (0.1mm); F is the residual penetration depth (0.1mm)

[0187] 2.5 Fluidity

[0188] Place the heated caulking glue into the mold frame on the tinplate, cool it at room temperature for 0.5h, then scrape it flat with a hot scraper and cool it for another 2h to make a test piece. Then place the tinplate together with the test piece in a 60±1℃ oven for 5h to measure its fluidity.

[0189] 2.6 Low temperature tensile test

[0190] Pour the heated caulking glue into the specimen. Since the caulking glue prepared this time is suitable for the Northeast region, 30℃ is selected as the test condition. The specimen is kept warm at 30℃ for 4h. The specimen is stretched to 22.5mm at 0.05mm / min on a tensile testing machine. After completion, take it out and check whether there is any crack ≥3mm. If there is, it is unqualified. Otherwise, it is placed at room temperature and compressed to 15mm under its own weight. Re-stretch the specimen and repeat 3 sets of cycles.

[0191] 3. Experimental design for the Northeast region

[0192] Because the main use area of ​​the caulking glue designed this time is the Northeast region, where the average daily minimum temperature in January in Heilongjiang Province is 25℃, the average daily minimum temperature in January in Jilin Province is 20℃, and the average daily minimum temperature in January in Liaoning Province is 18℃. Therefore, after conducting the tests required by the specifications, a series of test designs for the Northeast region are proposed in combination with the actual project conditions and regional characteristics. First of all, according to the on-site investigation, the working temperature of the caulking machine is about 190℃ when caulking. Considering human factors, the caulking glue needs 2 to 4 hours to be used up, so its short-term aging needs to be considered before conducting the caulking glue test; for the caulking glue, its own viscosity will affect the caulking rate during caulking. The high-viscosity caulking glue has a low spray rate and condenses faster, while the low-viscosity caulking glue has a high spray rate and condenses slower. On the other hand, viscosity will also affect the working bonding performance of the caulking glue. Low viscosity has good bonding performance, while high viscosity has poor bonding performance. During the use of caulking glue in the Northeast region, factors such as rainfall and freeze-thaw cycles in spring and autumn will affect the bonding performance of the caulking glue. Therefore, the design considers low-temperature stretching after immersion in water, and tensile testing after freeze-thaw cycles.

[0193] 3.1 Short-term construction aging simulation and low-temperature stretching

[0194] Since the caulking glue needs to be heated and kept at 190 degrees Celsius for 2 to 4 hours during the construction process, there is a problem that the caulking glue will age in the short term if the heating time is too long. This affects the use of the caulking glue. Therefore, an aging test is designed: first, the indoor simulated aging temperature is determined to be 190°C according to the temperature of the caulking glue heating and insulation, and the aging time is determined to be 4h according to the insulation time during construction. Therefore, the caulking glue is placed in an oven and kept at 190°C for 4h. At the same time, refer to the test in the specification for low-temperature stretching after short-term aging.

[0195] 3.2 Viscosity

[0196] The test uses a Brookfield viscometer to measure the viscosity of the caulking glue. The rotor and sample cylinder are placed in a temperature-controlled oven for insulation for 1.5 hours. The two are installed on the viscometer and the rotor is inserted into the sample cylinder to the specified height. The caulking glue is kept warm in the thermostat for at least 15 minutes. The rotor speed is adjusted so that the torque reading is maintained in the range of 10% to 98%. The viscosity changes are observed, and the readings are taken every 60 seconds for three consecutive times. The average value is taken as the measured value.

[0197] 3.3 Injection depth test

[0198] Two hamburger rutting specimens (320mm×260mm×50mm) were assembled to simulate crack conditions. Dust and other powders were sprinkled on the surfaces of the two hamburger rutting specimens to simulate the crack interface conditions. Then the two samples were placed opposite each other, with a distance of 15cm between the two rutting specimens to simulate the actual width of the road cracks. Then the preheated caulking glue was slowly poured into the gap, and the caulking glue was allowed to penetrate for 2 hours after pouring. Finally, the two hamburger rutting specimens bonded together by the caulking glue were restored to two pieces along the cracks, and five maximum depths were randomly selected at the bonding interface position for recording, and the average value was finally obtained as the caulking glue injection depth.

[0199] 3.4 Freeze-thaw cycle test

[0200] The sandwich specimens used in the reference specification and the reference test

[47] divided the test into two steps: cold treatment and heat treatment. For the heat treatment, the sandwich test piece was placed in an oven for at least 4 hours, and the oven temperature was set to 60°C. Then, the caulking glue was compressed under its own weight. After that, the heat treatment was completed after cooling at room temperature for 6 hours. In this test, 15°C was selected as the cold treatment temperature considering the winter temperature in Northeast China. The heat-treated specimen was placed in an environmental chamber for no less than 4 hours, and the temperature was set to 15°C. Then, the UTM testing machine was used for stretching at a stretching rate of 1.5 mm / min. The specimen was stretched to 150% of the casting width (22.5 mm). Then, it was fixed by a positioning block with a width of 22.5 mm. At room temperature for 6 hours, the caulking glue between the substrates was able to maintain a certain stretching amplitude, thus completing a freeze-thaw cycle. Then, the next freeze-thaw cycle test was carried out, and the number of freeze-thaw cycle tests was 3 cycles. Its adhesion was tested during the test.

[0201] 4. Results and Discussion

[0202] 4.1 Preparation and optimization of severe cold weather caulking glue

[0203] 4.1.1 Experimental design and test results based on RSM

[0204] The response surface methodology was used to study the effects of the content of SBS modifier, the content of furfural extracted oil, and the content of basalt fiber on several test indicators of caulking adhesive. The test group consisting of 17 experiments designed by the response surface test reduced the number of experiments while increasing certain accuracy and predictability compared to the traditional orthogonal test. The table details the influencing factors and their response results in the experimental design using the response surface. Among them, sc (SBS content), DC (extract content), BFC (basalt fiber contnet), a series of parameters that affect the preparation of caulking adhesive, are considered to be independent variables, and softening point, cone penetration, and compression elastic recovery rate are response variables or dependent variables.

[0205]

[0206] 4.1.2 Statistical analysis and discussion

[0207] In order to accurately predict the model (softening point, cone penetration, compression elastic recovery rate), an appropriate regression model was developed according to Table 6. According to Table 6, the softening point, cone penetration, and compression elastic recovery rate can be simulated in terms of performance. It can be seen that these conditions are optimal for making the model appropriate. For the modeling in this study, the applicability and appropriateness of the final model were evaluated through residual analysis, lack of fit test, outlier impact assessment and other methods.

[0208] Table 6 Evaluation parameter values ​​of the developed model

[0209]

[0210] 4.1.3 Variance Analysis of Prediction Model

[0211] Analysis of variance (ANOVA) is used to evaluate the performance of the prediction model. In Table 7, the F value in the model shows that the model has a certain degree of accuracy with a 95% confidence interval. Only 0.01% error is caused by possible noise. When performing a misfit test, the F value shows that the misfit is not significant relative to the pure error, which is caused by Figure 5 It shows that the standardized residuals are almost on a straight line, covering almost all the data Figure 6 The results of the comparison between the standardized residuals and the predicted values ​​are presented. Figure 7 The distribution of the residuals presented in also shows that the variance of the test values ​​itself does not have a fixed trend. Therefore, there is no obvious evidence to show that the model obtained by fitting is inappropriate. In order to make the prediction model more accurate Figure 8The prediction values ​​and comparison values ​​of these models are presented, and the optimal values ​​of the adjusted determination coefficients are shown. It can be found that the prediction models have a good fit for the above experimental parameters.

[0212] Table 7 Variance analysis parameters of softening point, cone penetration, and compression elastic recovery rate in the final model

[0213]

[0214]

[0215] 4.1.4 Sensitivity analysis of prediction model

[0216] The coefficient estimate represents the change in the expected response caused by a unit change in the factor under the premise that other influencing factors remain unchanged. For multiple regression problems, for independent variables with strong correlation, multicollinearity will occur between the independent variables. It becomes difficult to effectively calculate the regression coefficient. The variance inflation factor (VIF) is used to determine whether there is multicollinearity. VIF < 10 indicates that there is no multicollinearity. Therefore, it can be found from Table 8 that the VIFs of these model factors are close to 1, which shows that there is no multicollinearity in the model. Therefore, from the softening point correlation in Table 8, it can be seen that the SBS content and the basalt fiber content are important factors in the softening point prediction model. At the same time, the SBS content and the basalt fiber content appear in all the interactive factors, so these two influencing factors can be used as important factors in the softening point prediction model. According to the cone penetration correlation in Table 8, it can be seen that the SBS content and the furfural extracted oil content have an important influence on the cone penetration prediction model and are its influencing factors. At the same time, the interaction between SBS content and basalt fiber content is also an influencing factor of cone penetration; according to the correlation between compression elastic recovery rate in Table 8, SBS content is an important influencing factor, and the interaction between SBS content and furfural extracted oil content also has an impact on it.

[0217] Table 8 Sensitivity analysis of effective factors

[0218]

[0219] 4.1.4 Response surface analysis among factors

[0220] from Fig. 9 It can be seen that with the increase of SBS content, the softening point temperature increases significantly, with the increase of furfural extracted oil, the softening point increases but is relatively limited, and with the increase of basalt fiber content, the softening point decreases first and then increases but is relatively limited; Fig.10It can be found that with the increase of furfural extracted oil, the cone penetration increases significantly. With the increase of SBS content, the cone penetration increases gradually and then decreases, but the change is relatively small. With the increase of basalt fiber, the cone penetration decreases significantly. Fig.11 It can be seen that with the significant increase of SBS content and basalt fiber content, the compression elastic recovery rate also increases accordingly, and with the increase of furfural extracted oil, the compression elastic recovery rate tends to decrease.

[0221] 4.1.5 Model and specification verification

[0222] In order to verify the accuracy of the prediction results of the response surface method, considering that the softening point is too low to meet the high ground temperature in the Northeast region in summer, and too high may cause waste of materials, the optimal softening point temperature range is selected as 90-95°C. In order to ensure excellent resistance to foreign body invasion and rapid recovery of deformation, the cone penetration value is selected to be the minimum, and the compression elastic recovery rate is selected to be the maximum to obtain the optimal ratio. While verifying its results, its fluidity and low-temperature tensile cycle are tested to see if they meet the requirements. The results are shown in Table 9. From the results, the prediction results are consistent with the test results and also meet the requirements in the specifications. This shows that the use of RSM to optimize the preparation parameters of the caulking glue has relatively good accuracy.

[0223] Table 9 Optimal preparation parameters and prediction and experimental comparison

[0224]

[0225] 4.2 Test results in Northeast China

[0226] In order to evaluate the use of the caulking glue prepared by RSM with SBS and rubber powder and added basalt fiber in the Northeast region, which is characterized by high temperature, high cold and sufficient precipitation. It was compared with the caulking glue prepared by SBS composite rubber powder commonly used in the Northeast and two cold-type caulking glues (suitable for 30°C) purchased on the market. The preparation process of SBS composite rubber powder is basically the same as that of the caulking glue in this article. The same 20% rubber powder modified asphalt is selected as the matrix, the SBS content is 9.9%, and the furfural extracted oil is 14.9% for preparation.

[0227] 4.2.1 Short-term construction aging and low-temperature stretching

[0228] The short-term aging simulation of the caulking adhesive was carried out, and after the short-term aging, its basic performance was tested according to the specifications to see if it met the requirements. The results are shown in Table 10. It can be seen from the table that the basalt fiber modified caulking adhesive has a higher softening point and a better compression elastic recovery rate, which may be related to the spatial network structure formed by the basalt fiber in the caulking adhesive. However, its cone penetration decreases a lot after aging, which is related to the fact that the basalt fiber forms a network structure in it, resulting in a harder texture and the evaporation of other modifiers during the aging process.

[0229] Table 10 Comparison of basalt fiber modified caulking glue and other caulking glue before and after aging

[0230]

[0231] Table 11 Maximum adhesion before and after aging

[0232]

[0233] Table 11 and Fig.12 , 13 It can be seen that with the increase of the number of low-temperature stretching cycles, the maximum adhesion shows a significant downward trend. At the same time, it can be found that the adhesion of the caulking glue after aging also decreases significantly, which shows that short-term aging has a significant effect on the working performance of the caulking glue. Among them, the adhesion of the three caulking glues B, C, and D has a significant attenuation with aging and low-temperature stretching cycles. Among them, the average decrease in low-temperature stretching cycles (comparison of the maximum and minimum values ​​of the cyclic adhesion) reaches 31.3%, and the largest decrease in adhesion after low-temperature stretching cycles is C, reaching 45.8%; the average decrease in caulking glue before and after aging (the third cycle) reaches 37.26%. The largest decrease before and after aging is C, reaching 67.9%. For A, that is, the modified caulking glue with basalt fiber added, it can be found that its own adhesion is much greater than that of other caulking glues. Secondly, the adhesion of the basalt fiber modified caulking glue does not decrease significantly with the low-temperature stretching cycle. At the same time, the maximum decrease in adhesion after aging is only 5%. This may be because, on the one hand, the addition of basalt fiber forms a spatial network structure, which increases its tensile strength. Secondly, the basalt fiber-modified caulking adhesive increases the contact points between the adhesive and the asphalt mixture, increases the contact area, and significantly increases the adhesion.

[0234] 4.2.2 Viscosity

[0235] like Fig.14The viscosity-temperature curves of four types of caulking glue at 160℃~190℃ are shown. It can be seen from the figure that with the increase of temperature, the viscosity of the four types of caulking glues all decrease significantly. Compared with B, which is modified caulking glue without basalt fiber, the viscosity of A is significantly higher, which shows that the addition of basalt fiber can increase its viscosity. Compared with C and D, the viscosity of A is smaller. Considering that too high viscosity will affect the flow of caulking glue during injection, and low viscosity will affect its adhesion, the viscosity of the modified caulking glue mixed with basalt fiber is moderate.

[0236] 4.2.3 Filling depth

[0237] The depth of caulking glue is as follows: Fig.15 As shown in the figure, the injection depth of sample B is the deepest and the injection depth of sample D is the shallowest. The deeper the injection depth, the better the contact with the interface and the better the working performance. The injection depth of sample A containing basalt fiber is better than that of D but slightly inferior to that of C, indicating that the addition of basalt fiber does not have an adverse effect on its working performance.

[0238] 4.2.4 Freeze-thaw cycles

[0239] like Fig.16 It can be found that freeze-thaw cycles have a huge impact on adhesion. Fig.12 In low temperature stretching, the adhesion of samples B, C, and D not only decreased significantly, but also the displacement adhesion curve changed significantly. This may be due to the reciprocating freeze-thaw cycle, which caused some structural damage to the inside of the caulking glue. However, the curve of sample A (caulking glue mixed with basalt fiber) did not change significantly after the freeze-thaw cycle. At the same time, it can be seen from Table 12 that the adhesion of samples BCD decreased by an average of 19.3% with the freeze-thaw cycle, and the largest decrease was 30% for sample D. Sample A only decreased by 12.5%. Overall, the modified caulking glue A mixed with basalt fiber has good freeze-thaw resistance.

[0240] Table 12 Changes in adhesion during freeze-thaw cycles

[0241]

[0242] 5. Conclusion

[0243] 1. Based on response surface analysis, SBS, furfural extracted oil and basalt fiber will increase the softening point of the caulking glue; the increase of furfural extracted oil will significantly increase the cone penetration, the increase of basalt fiber content will significantly reduce the cone penetration, and the interaction between SBS content and cone penetration is not obvious; the increase of SBS and basalt fiber content will increase the compression elastic recovery rate of the caulking glue.

[0244] 2. Based on the response surface, a reliable regression prediction model was established, and the expected target in the independent variable (influencing factor) and the dependent variable (performance response) was used. That is, a modified asphalt with 20% rubber powder content was used as the base asphalt, 9.9% SBS, 14.9% furfural extracted oil, and 1.65% basalt fiber were added to obtain a better basalt fiber modified asphalt caulking glue.

[0245] 3. Through a series of tests simulating the construction and use of caulking glue in Northeast China, including short-term construction aging simulation, low-temperature stretching, viscosity, injection depth, and freeze-thaw cycles, it is proved that basalt fiber modified asphalt caulking glue has good high and low temperature performance, among which the low-temperature adhesion after short-term aging decreases to only 5%, which is lower than the average of 37.62%. After freeze-thaw cycles, the adhesion decreases to only 12.5%, which is lower than the average of 19.3%. At the same time, the performance is also better, and its viscosity and injection depth are not significantly inferior to other similar products.

[0246] The formula of the caulking glue in Example 1 is as follows: 1 kg of rubber modified asphalt, 99 g of SBS modifier, 143 g of furfural extracted oil, 15 g of basalt fiber, and 70 g of dibutyl phthalate.

[0248] The formula of the caulking glue in Example 2 is as follows: 2 kg of rubber modified asphalt, 198 g of SBS modifier, 286 g of furfural extracted oil, 30 g of basalt fiber, and 140 g of dibutyl phthalate.

[0249] Example 3 The formula of the caulking glue is as follows: 1 kg of rubber modified asphalt, 99 g of SBS modifier, 143 g of furfural extracted oil, 70 g of dibutyl phthalate

[0250] Comparative Example 1

[0251] Take the commonly used caulking glue suitable for low temperature environment in the market as comparative example 1

[0252] Comparative Example 2

[0253] Take the commonly used caulking glue suitable for high temperature environment in the market as comparative example 2

[0254] Comparative Example 3

[0255] Example 1 is basically free of dibutyl phthalate, and the remaining components and amounts are the same as those of Example 1.

[0256]

[0257] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A wide temperature range caulking adhesive based on rubber modified asphalt, characterized in that: include: The matrix material is rubber modified asphalt, and the additives are basalt fiber, rubber powder, SBS, dibutyl phthalate, and furfural extracted oil.

2. A method for preparing a wide temperature range caulking adhesive based on rubber modified asphalt as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Place the rubber-modified asphalt in an oven and heat it at 150°C to a fluid state; Step 2: Add furfural extracted oil and dibutyl phthalate to the sample, and stir at a speed of 800 r / min for 30 minutes on a high-speed stirring disperser at 165-175°C; Step 3: Add SBS to the sample in batches and stir at 2000r / min for 30 minutes on a high-speed stirring disperser at 165-175°C; Step 4: Shear the sample at a speed of 4000 r / min for 45 minutes on a high-speed stirring disperser at 175°C; Step 5: Add basalt fiber to the sample in batches, and shear the sample at a speed of 4500r / min-5000r / min on a high-speed stirring disperser at 175-180°C for at least 30 minutes to ensure that there are no obvious impurities and suspension.

3. The method for preparing a wide temperature range caulking adhesive based on rubber modified asphalt according to claim 2, characterized in that: The SBS is added in at least two times, and after each addition, the mixture is stirred at a temperature of 165-175° C. and a speed of 2000 r / min for 30 minutes.

4. The method for preparing a wide temperature range caulking adhesive based on rubber modified asphalt according to claim 2, characterized in that: In step 5, in order to ensure uniform distribution of the basalt fibers, the shearing operation includes adding the basalt fibers in batches according to weight, and performing high-speed shearing for at least 5 minutes after each addition.

5. The method for preparing a wide temperature range caulking adhesive based on rubber modified asphalt according to claim 2, characterized in that: The blending amounts of the furfural extracted oil and dibutyl phthalate are adjusted according to the type of asphalt and the severity of the coldness of the intended use environment to ensure that the final product maintains excellent physical properties within a wide temperature range.

6. A preparation system for a wide temperature range caulking adhesive for rubber-modified asphalt, characterized in that: The system comprises: A heating module is used to place the rubber-modified asphalt in an oven and heat it to a fluid state at 150°C; A stirring module is used to stir the mixed sample of furfural extracted oil and dibutyl phthalate at a speed of 800 r / min for 30 minutes on a high-speed stirring disperser at 165-175°C, and to stir the sample added with SBS at a speed of 2000 r / min for 30 minutes at the same temperature; The shearing module is used to shear the sample at a speed of 4000 r / min for 45 minutes on a high-speed stirring disperser at 175°C, and to shear the mixture of basalt fiber and sample at a speed of 4500 r / min to 5000 r / min at a temperature of 175 to 180°C for at least 30 minutes to ensure the uniformity of the sample and the absence of obvious impurities.

7. The preparation system of the wide temperature range caulking adhesive for rubber modified asphalt according to claim 6, characterized in that: The system further includes a control module for controlling the operating parameters of each module, including temperature, rotation speed, and time, to ensure the accuracy and stability of the preparation process.

8. The system for preparing the wide temperature range caulking adhesive for rubber modified asphalt according to claim 6, characterized in that: The system also includes a monitoring module for real-time monitoring of temperature, shear force and mixing uniformity during the preparation process, and adjusting system parameters through a feedback mechanism to achieve the best preparation effect.

9. The system for preparing the wide temperature range caulking adhesive for rubber modified asphalt according to claim 6, characterized in that: The system also includes a data storage module for storing parameter data in each preparation step for use in subsequent analysis and optimization of the caulking glue formula.

Citation Information

Cited By

  • Road maintenance method and system based on high-elasticity pouring sealant

    CN119991096A

  • A road maintenance method and system based on highly elastic potting compound

    CN119991096B

  • Severe cold low-density road crack pouring sealant and preparation method thereof

    CN120944524A

  • Wide-temperature-range flexible modified asphalt and preparation method thereof

    CN121873568A